Blow Your Nose, Shrimp! Unexpectedly Dense Bacterial Communities Occur on the Antennae and Antennules of Hydrothermal Vent Shrimp - Zbinden, Magali; Gallet, Alison; Szafranski, Kamil M.; Machon, Julia; Ravaux, Juliette; Léger, Nelly; Duperron, Sébastien (Frontiers in Marine Science, 2018)
In crustaceans, as in other animals, perception of environmental cues is of key importance for a wide range of interactions with the environment and congeners. Chemoreception involves mainly the antennae and antennules, which carry sensilla that detect water-borne chemicals. The functional importance of these as exchange surfaces in the shrimp's sensory perception requires them to remain free of any microorganism and deposit that could impair the fixation of odorant molecules on sensory neurons. We report here the occurrence of an unexpected dense bacterial colonization on surface of the antennae and antennules of four hydrothermal vent shrimp species. Microscopic observation, qPCR and 16S rRNA barcoding reveal the abundance, diversity and taxonomic composition of these bacterial communities, that are compared with those found on a related coastal shrimp. Bacterial abundances vary among species. Bacteria are almost absent in coastal shrimp, meanwhile they fully cover the antennal flagella in some hydrothermal vent species. Epsilon- and Gammaproteobacteria dominate the hydrothermal shrimp-associated communities, whereas Alphaproteobacteria and Bacteroidetes are dominant in the coastal ones. Bacteria associated with vent shrimp species are most similar to known chemoautotrophic sulfur-oxidizers. Potential roles of these bacteria on the hydrothermal shrimp antennae and antennules and on sensory functions are discussed.